KNOWLEDGE, ATTITUDE, REFERENCE GROUP, AND BEHAVIOR OF DIPHTHERIA IMMUNIZATION IN RURAL AND URBAN AREAS - Ajeng Prameswari; Retnaningsih (Journal of Child, Family, and Consumer Studies, 2023)
Diphtheria is an infectious disease that has been an epidemic in Indonesia and has an average mortality rate of 5-10 percent for children under five years of age. This study aims to 1) analyze the differences and relationships of maternal characteristics, family characteristics, knowledge, attitudes, and reference groups with diphtheria immunization behavior in rural and urban areas; and 2) analyze the effect of maternal characteristics, family characteristics, knowledge, attitudes, and reference groups on diphtheria immunization behavior. This study used a cross-sectional study design. The sample was 41 mothers with children aged 5-12 months and purposively selected at one of the Integrated Services Post in Bogor City and Bogor Regency. The data obtained were processed through coding, input, cleaning, analysis, and interpretation of data. The results showed differences between knowledge, attitude, reference group, and behavior of diphtheria immunization in rural and urban areas. The factor associated with the completeness of diphtheria immunization is social media for rural areas, while it does not exist in urban areas. Factors associated with compliance with the immunization schedule were family size, attitude, interpersonal, and expert for rural areas, and years of education for urban areas. Factors that influence the completeness of immunization are the length of education, attitudes, and interpersonal reference groups. Based on the results of this study, a cross-sectoral role is needed to support community education and educate mothers regarding diphtheria immunization.